Chimerism Analysis of Cell-Free DNA in Patients Treated with Hematopoietic Stem Cell Transplantation May Predict Early Relapse in Patients with Hematologic Malignancies. (23rd February 2016) - Aljurf, Mahmoud; Abalkhail, Hala; Alseraihy, Amal; Mohamed, Said Y.; Ayas, Mouhab; Alsharif, Fahad; Alzahrani, Hazza; Al-Jefri, Abdullah; Aldawsari, Ghuzayel; Al-Ahmari, Ali; Belgaumi, Asim F.; Walter, Claudia Ulrike; et al.
Abstract : Background . We studied DNA chimerism in cell-free DNA (cfDNA) in patients treated with HSCT. Methods . Chimerism analysis was performed on CD3+ cells, polymorphonuclear (PMN) cells, and cfDNA using 16 small tandem repeat loci. The resulting labeled PCR-products were size-fractionated and quantified. Results . Analyzing samples from 191 patients treated with HSCT for nonneoplastic hematologic disorders demonstrated that the cfDNA chimerism is comparable to that seen in PMN cells. Analyzing leukemia patients (N = 126) showed that, of 84 patients with 100% donor DNA in PMN, 16 (19%) had evidence of clinical relapse and >10% recipient DNA in the plasma. Additional 16 patients of the 84 (19%) showed >10% recipient DNA in plasma, but without evidence of relapse. Eight patients had mixed chimerism in granulocytes, lymphocytes, and plasma, but three of these patients had >10% recipient DNA in plasma compared to PMN cells and these three patients had clinical evidence of relapse. The remaining 34 patients showed 100% donor DNA in both PMN and lymphocytes, but cfDNA showed various levels of chimerism. Of these patients 14 (41%) showed laboratory or clinical evidence of relapse and all had >10% recipient DNA in cfDNA. Conclusion . Monitoring patients after HSCT using cfDNA might be more reliable than cellular DNA in predicting early relapse.